Paralinguistic Features in Cross-Cultural Communication: A Study of Indonesian-Japanese Married Couples in Vlogs - Widia Hastuti, Wina; Widianti, Susi (Chi e Journal of Japanese Learning and Teaching, 2025)
Paralinguistics forms an essential part of nonverbal communication and plays a crucial role in shaping meaning within intercultural contexts. Grounded in Poyatos’ (2002) framework of paralinguistic aspects, this study examines how paralinguistic features are realized in the interactions of an Indonesian Japanese married couple through their vlog. Using a qualitative descriptive approach with note-taking techniques, the research identifies and analyzes features such as voice volume, pitch, tempo, pauses, drawling, and clipping. The findings reveal distinct tendencies that reflect each speaker’s cultural background. The Indonesian speaker, Diera, often employs soft loudness, higher pitch, drawling, and frequent pauses, expressing warmth and enthusiasm characteristic of Indonesian communicative norms. Her Japanese husband, by contrast, displays a slower tempo, moderate volume, and subtle pitch variation—traits associated with calmness, politeness, and harmony in Japanese communication. These contrasting yet complementary paralinguistic patterns demonstrate how intercultural couples negotiate meaning and emotional expression through nonverbal cues. The study highlights the significance of understanding paralinguistic elements in cross-cultural communication, particularly for enhancing mutual comprehension, preventing misinterpretation, and fostering more effective interaction across cultural boundaries.